Copper thiovanadate-based materials, methods of preparation, and applications in magnesium secondary batteries
Patent Information
- Application Number
- CN202611005025.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-27
AI Technical Summary
这些杂质相难以通过简单的洗涤去除,会严重破坏晶体结构的完整性,导致材料的比容量和循环稳定性大幅下降
[0006]有益效果:本方案通过水热法合成硫代钒酸铜基材料,反应温度相对更低,生产成本更加低廉,且有机大分子的浓度范围为0.083%-3.23%,在实际生产中,无需配备高精度的计量设备,即使在原料配比存在0.083%-3.23%的波动范围内,仍能一步法获得高纯度的目标产物,保证了批次间电化学性能的稳定性,为镁离子电池正极材料的低成本、大规模工业化生产提供了切实可行的解决方案。
Smart Images

Figure CN122977439A_ABST
Abstract
Description
Technical Field
[0001] This solution relates to the field of battery materials technology, specifically to copper thiovanadate-based materials, their preparation methods, and their application in magnesium secondary batteries. Background Technology
[0002] To address the scarcity of lithium resources and the safety hazards posed by lithium dendrites, magnesium, located diagonally opposite lithium in the periodic table, possesses similar chemical properties. However, compared to lithium, magnesium boasts significant advantages such as abundant resources, simple synthesis processes, and low cost. Furthermore, magnesium is relatively stable in air as a negative electrode material, making it less prone to dendrite formation and greatly enhancing battery safety. Therefore, the development of high-performance magnesium-ion batteries holds broad prospects. However, its positive electrode, negative electrode, and electrolyte still present a series of challenges. For instance, magnesium ions have a small ionic radius and high charge density, making the positive electrode material prone to binding with solvents, leading to severe solvation. Moreover, only a few positive electrode materials can effectively achieve reversible insertion / extraction of magnesium ions. Transition metal sulfides are considered the most promising positive electrode materials for magnesium-ion batteries due to their unique properties. Among them, Cu3VS4, a typical vanadium-based sulfide, possesses advantages such as three-dimensional ion channels conducive to magnesium ion diffusion, multi-electron reaction potential, and excellent diffusion kinetics, leading to its widespread promotion and application in magnesium-ion battery positive electrode materials. However, the high-temperature solid-state synthesis method for preparing Cu3VS4 requires long-term annealing at temperatures of 500°C to 800°C, which not only increases production costs but also easily leads to excessive grain growth and severe particle agglomeration, resulting in a decrease in the specific surface area and electrochemical active sites of the material, which is not conducive to the rapid transport of magnesium ions.
[0003] To lower the reaction temperature, researchers attempted a liquid-phase synthesis method, but this method is extremely sensitive to the stoichiometric ratio of the raw materials. Due to the different reactivity of copper and vanadium in solution, even a slight deviation in the raw material ratio can easily generate impurity phases such as CuS and Cu₂S. These impurity phases are difficult to remove with simple washing, severely disrupting the integrity of the crystal structure and leading to a significant decrease in the material's specific capacity and cycling stability. Summary of the Invention
[0004] The present invention aims to provide copper thiovanadate-based materials and their preparation methods to replace Cu3VS4 and reduce the production cost of the materials.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: a copper thiovanadate-based material is prepared by adding a copper source, a vanadium source, and a sulfur source to an organic macromolecular solution using water as a solvent, followed by hydrothermal reaction and centrifugal drying. The molar ratio of Cu, V, and S elements provided by the copper source, vanadium source, and sulfur source is 3:1:12. The concentration of organic macromolecules in the organic macromolecular solution ranges from 0.083% to 3.23% by mass percentage, and the ratio of Cu provided by the copper source to water in the organic macromolecular solution is 1 millimole: 1 milliliter.
[0006] Beneficial effects: This method synthesizes copper thiovanadate-based materials via a hydrothermal process, which has a relatively lower reaction temperature and lower production cost. Furthermore, the concentration range of organic macromolecules is 0.083%-3.23%. In actual production, there is no need to equip high-precision metering equipment. Even if the raw material ratio fluctuates within the range of 0.083%-3.23%, a high-purity target product can still be obtained in one step, ensuring the stability of electrochemical performance between batches. This provides a practical and feasible solution for the low-cost, large-scale industrial production of magnesium-ion battery cathode materials.
[0007] Furthermore, the organic macromolecular solution is prepared by ultrasonically dissolving any one or a combination of at least two of the following: decaalkyltrimethylammonium bromide, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, heptadecanyltrimethylammonium bromide, and octadecyltrimethylammonium bromide in deionized water.
[0008] Furthermore, the copper source is any one or a combination of at least two of copper fluoride, copper chloride, copper bromide, copper nitrate, copper sulfate, copper carbonate, copper oxalate, copper acetate, basic copper carbonate, copper hydroxide, copper oxide, copper sulfide, and copper acetylacetonate.
[0009] Furthermore, the vanadium source is any one or a combination of at least two of ammonium metavanadate, vanadium acetylacetonate, and sodium orthovanadate.
[0010] Furthermore, the sulfur source is any one or a combination of at least two of thioacetamide, thiourea, and L-cysteine.
[0011] Furthermore, the hydrothermal reaction temperature is 160-230℃, and the reaction time is 18-72 hours.
[0012] This invention also includes a method for preparing copper thiovanadate-based materials, comprising the following steps: S1 solution is prepared by dissolving organic macromolecules in deionized water to obtain an organic macromolecule solution, wherein the concentration of organic macromolecules ranges from 0.083% to 3.23% by mass percentage. In the S2 hydrothermal reaction, copper, vanadium, and sulfur sources are added to the organic macromolecular solution prepared in S1, and the reaction is carried out at 160-230℃ for 1-3 days. The molar ratio of Cu, V, and S provided by the copper, vanadium, and sulfur sources is 3:1:12, and the ratio of Cu in the copper source to deionized water in the organic macromolecular solution is 1 mmol: 1 mL. S3 Centrifugation and Drying: After cooling the solution from step S2, centrifugation and drying are performed sequentially to obtain copper thiovanadate-based material.
[0013] Furthermore, in S3, during centrifugation, deionized water and ethanol are used alternately for 2-5 centrifugations at a speed of 8000-12000 rpm, with each centrifugation lasting 2-10 minutes. The supernatant is discarded after each centrifugation.
[0014] Furthermore, in S3, the drying process conditions are: drying in a vacuum oven at 50-70℃ for 10-15 hours, with the vacuum degree of the vacuum oven not lower than 0.09 MPa.
[0015] This scheme also includes the application of copper thiovanadate-based materials obtained according to the aforementioned preparation method in magnesium secondary batteries. Attached Figure Description
[0016] Figure 1 The XRD comparison diagrams are of the materials prepared with different amounts of organic macromolecules added in Example 1 of the present invention and Cu3VS4, CuS and Cu2S. Figure 2 In Example 1 of the present invention, a is an infrared image of the material prepared by adding different amounts of organic macromolecules, and b is a Raman image of the material prepared by adding different amounts of organic macromolecules in Example 1 of the present invention. Figure 3 XPS plots of Cu, V, and S in materials prepared with different amounts of added organic macromolecules in Example 1 of this invention; Figure 4 This is a comparison of the electrochemical performance curves of materials prepared with different amounts of organic macromolecules in Example 1 of the present invention at current densities of 200 mA / g and 2000 mA / g. Figure 5 This is a rate performance diagram of materials prepared with different amounts of organic macromolecules in Example 1 of the present invention; Figure 6 This is the XRD result diagram of sample 1 in Example 2 of the present invention; Figure 7 This is the XRD result diagram of sample 2 in Example 2 of the present invention; Figure 8 This is the XRD result diagram of sample 3 in Example 2 of the present invention; Figure 9 This is a SEM image of sample 1 from Example 2 of the present invention; Figure 10 This is an SEM image of sample 2 from Example 2 of the present invention; Figure 11 This is a SEM image of sample 3 from Example 2 of the present invention; Figure 12 This is a graph showing the electrochemical performance of sample 1 in Example 2 of the present invention at a current density of 200 mA / g. Figure 13 This is the electrochemical performance curve of Comparative Example 1 of the present invention at a current density of 100 mA / g; Figure 14 The electrochemical performance curve of Comparative Example 2 of the present invention at a current density of 200 mA / g is shown. Detailed Implementation
[0017] Example 1 The copper thiovanadate-based material is prepared by adding copper, vanadium, and sulfur sources to an organic macromolecular solution, followed by hydrothermal reaction and centrifugal drying. The molar ratio of Cu, V, and S provided by the copper, vanadium, and sulfur sources is 3:1:12. The concentration of the organic macromolecular solution, by mass percentage, ranges from 0.083% to 3.23%. Specifically, the organic macromolecular solution consists of any one or at least two of the following: decaalkyltrimethylammonium bromide, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, heptadecanyltrimethylammonium bromide, and octadecyltrimethylammonium bromide. The solution is prepared by ultrasonic dissolution in deionized water; the copper source is any one or a combination of at least two of copper fluoride, copper chloride, copper bromide, copper nitrate, copper sulfate, copper carbonate, copper oxalate, copper acetate, basic copper carbonate, copper hydroxide, copper oxide, copper sulfide, and copper acetylacetonate, and the copper source provides a Cu to water ratio of 1 mmol: 1 mL in the organic macromolecule solution; the vanadium source is any one or a combination of at least two of ammonium metavanadate, vanadium acetylacetonate, and sodium orthovanadate; the sulfur source is any one or a combination of at least two of thioacetamide, thiourea, and L-cysteine; the hydrothermal reaction temperature is 160-230℃, and the reaction time is 1-3 days.
[0018] The preparation method includes the following steps: S1 solution is prepared by dissolving organic macromolecules in deionized water to obtain an organic macromolecule solution, wherein the concentration of organic macromolecules ranges from 0.083% to 3.23% by mass percentage. In the S2 hydrothermal reaction, copper, vanadium, and sulfur sources are added to the organic macromolecular solution prepared in S1, and the reaction is carried out at 160-230℃ for 18-72 hours. The molar ratio of Cu, V, and S provided by the copper, vanadium, and sulfur sources is 3:1:12, and the ratio of copper source to water in the organic macromolecular solution is 1 mmol:1 mL. S3 Centrifugal Drying: After cooling the solution from step S2, centrifuge and dry it sequentially to obtain copper thiovanadate-based material. During centrifugation, deionized water and ethanol are used alternately for 2-5 centrifugations at a speed of 8000-12000 rpm for 2-10 min each time. The supernatant is discarded after each centrifugation. The drying process conditions are: drying in a vacuum oven at 50-70℃ for 10-15 h, with a vacuum degree of not less than 0.09 MPa.
[0019] Specifically, 50 mg, 100 mg, 500 mg, 1000 mg, and 2000 mg of organic macromolecules were added to 60 ml of deionized water, respectively, to obtain organic macromolecule solutions. 6 mmol of copper source, 2 mmol of vanadium source, and 24 mmol of sulfur source were weighed and added to the organic macromolecule solutions. After hydrothermal reaction and centrifugal drying, copper thiovanadate-based materials were obtained. The prepared copper thiovanadate-based materials were then subjected to XRD (X-ray diffraction) with Cu3VS4, CuS, and Cu2S, respectively. The crystal structure, molecular composition, surface chemical state, microstructure, and macroscopic electrochemical performance of the prepared copper thiovanadate-based materials were studied using infrared spectroscopy, Raman spectroscopy, XPS spectroscopy, electrochemical performance curve comparison, and rate performance diagrams. Figures 1-5 In the above, CT50, CT 100, CT 500, CT 1000 and CT 2000 are copper thiovanadate-based materials after adding 50 mg, 100 mg, 500 mg, 1000 mg and 2000 mg of organic macromolecule CTAB to 60 ml of deionized water, respectively.
[0020] like Figure 1 As shown, when the CTAB addition amount is 50, 100, 500, 1000, and 2000 mg, Cu3VS4, Cu3VS4@CuS, Cu3VS4@Cu2S, Cu3VS4@Cu2S, and Cu3VS4@Cu2S@S8 cathode materials can be prepared respectively. Figure 2 As shown in a, the CTAB peaks are generally located at 2964 and 293 cm⁻¹. 1 ,according to Figure 2 As shown in Figure a, no significant CTAB peak signal was detected in any of the five materials, and the amount of CTAB on the surface of the five materials was negligible. Figure 2 As shown in b, all five materials can be observed at 146, 202, 294, and 374 cm. 1 There are distinct characteristic peaks, corresponding to Cu-S bond stretching vibration, Cu-S bond bending vibration, VS bond stretching vibration, and VS bond bending vibration, respectively. For example... Figure 3As shown, XPS testing was not possible with CT2000 due to the presence of S8, and the XPS results only included four materials: CT50, CT100, CT500, and CT1000. (XPS full spectrum) Figure 3 a) The results show that characteristic peaks corresponding to Cu 2p, V 2p and S 2p can be clearly found in all four materials, and characteristic peaks of O 1s and C 1s are also present. Figure 3 As shown in b, the XPS spectra of Cu show that significant Cu is present in all four materials. + Characteristic peaks. In CT100, due to the low CuS phase content, the corresponding Cu... 2+ The characteristic peak signal is relatively weak. Spectral characteristics and valence state distribution of V and S ( Figure 3 c): V mainly exists in the form of +4 and +5 valence, while S exists in... 1 and Primarily divalent. For example... Figure 4 As shown, Figure 4 Five materials were tested at a current density of 200 mA / g. It was evident that CT100 and CT500 exhibited the best electrochemical performance. Subsequent long-cycle testing at a current density of 2 A / g revealed that CT50 showed the best long-cycle discharge capacity. The remaining materials, in descending order of capacity, were CT500, CT100, CT2000, and CT1000. Except for CT50, this order was largely consistent with the results of the initial charge-discharge tests. This is primarily because CT50, being a pure Cu3VS4 phase, has the longest activation process. Its discharge capacity is lower than other materials in the first 100 cycles, gradually increasing and surpassing them thereafter. Under low-rate testing conditions, CT50 failed to fully activate and reach its optimal performance state, while other materials reached their maximum capacity around 100 cycles. Therefore, CT50 demonstrated superior performance in long-cycle testing. Based on the maximum discharge capacity, the capacity retention rates after 1000 cycles are calculated as follows: CT50, CT100, CT500, CT1000, and CT2000 are 87%, 67%, 76%, 63%, and 74%, respectively. Figure 5 Among the five materials, CT100 and CT500 exhibited the best rate performance, with discharge capacities of 193 and 199, 178 and 186, 164 and 173, 144 and 147, 101 and 96, and 68 and 57 mAh / g at current densities of 0.2, 0.5, 1, 2, 5, and 10 A / g, respectively. When the current density returned to 0.2 A / g, the discharge specific capacities recovered to 194 and 204 mAh / g, respectively, which were still higher than those of the other materials.
[0021] Example 2 Based on Example 1, and to facilitate understanding by those skilled in the art, the following will describe this scheme in conjunction with the preparation process of samples 1-3 in the laboratory. The prepared products are as follows:
[0022] Sample preparation is as follows: 1) According to the table, hexadecyltrimethylammonium bromide was added to 60 ml of deionized water and ultrasonically vibrated until homogeneous to obtain mixed solution 1. Copper source, vanadium source, and sulfur source were then ground separately using a mortar and pestle and added to the mixed solution to obtain mixed solution 2. The molar ratio of copper, vanadium, and sulfur provided by the copper, vanadium, and sulfur sources was 3:1:12.
[0023] 2) Transfer the mixed solution 2 obtained in step 1) to the reaction vessel, heat it to 180 ℃, and react at the reaction temperature of 180 ℃ for 18 hours. After the reaction is completed, cool it to room temperature to obtain the reaction solution. 3) Take the cooled reaction solution and place it in a centrifuge tube. Centrifuge it three times with deionized water and ethanol alternately at a speed of 10,000 rpm for 8 minutes each time. Remove the supernatant. Then dry the centrifuged solid in a vacuum oven at 60°C for 12 hours to obtain the copper thiovanadate-based material of samples 1-3.
[0024] Comparative Example 1 The preparation method of Comparative Example 1 is as follows: 1) Grind the copper source, vanadium source, and sulfur source separately in a mortar and pestle, and then add them to 60 ml of deionized water. The molar ratio of copper, vanadium, and sulfur is 3:1:12. After stirring evenly at room temperature, adjust the pH of the system to 2.9 with ammonia water to obtain a mixed solution. The copper source is copper chloride, the vanadium source is ammonium metavanadate, and the sulfur source is thiourea. 2) Transfer the mixed solution obtained in step 1) to a reaction vessel; heat to 180 ℃ and react at the reaction temperature of 180 ℃ for 18 hours. After the reaction is completed, cool to room temperature to obtain the reaction solution. 3) Take the cooled reaction solution and place it in a centrifuge tube. Centrifuge it three times with deionized water and ethanol alternately at a speed of 10,000 rpm for 8 minutes each time. Remove the supernatant. Then dry the centrifuged solid in a vacuum oven at 60°C for 12 hours to obtain vanadium-based sulfide Cu3VS4 for magnesium-ion batteries.
[0025] Comparative Example 2 The preparation method of Comparative Example 2 is as follows: 1) Grind the copper source and sulfur source separately in a mortar and pestle, and then add them to 60 ml of deionized water. The molar ratio of copper to sulfur is 1:1.5. Stir the mixture at room temperature to obtain a mixed solution. The copper source is copper nitrate and the sulfur source is thiourea. 2) Transfer the mixed solution obtained in step 1) into a 100ml reaction vessel liner and place it into the reaction vessel. Heat to 180 ℃ and react at 180 ℃ for 18 hours. After the reaction is complete, cool to room temperature to obtain the reaction solution; 3) Take the cooled reaction solution and place it in a centrifuge tube. Centrifuge it three times with deionized water and ethanol alternately at a speed of 10,000 rpm for 8 minutes each time. Remove the supernatant. Then dry the centrifuged solid in a vacuum oven at 60°C for 12 hours to obtain copper sulfide for magnesium-ion batteries.
[0026] Performance characterization: The crystal structure of samples 1-3 was determined using an XRD diffractometer. The XRD patterns of the structures of samples 1-3 are as follows: Figure 6 , Figure 7 , Figure 8 As shown in the figure, when the amount of hexadecyltrimethylammonium bromide added is 100, 500 and 2000 mg respectively, Cu3VS4@CuS, Cu3VS4@Cu2S and Cu3VS4@Cu2S@S8 cathode materials can be obtained, indicating that the amount of different organic macromolecules added will affect the phase composition of copper thiovanadate-based materials.
[0027] Micromorphology The microstructure of samples 1-3 was tested using a scanning electron microscope. The results are shown in the figure. Figure 9 , Figure 10 , Figure 11 As shown, Figure 9 , Figure 10 , Figure 11 As shown, when the amount of hexadecyltrimethylammonium bromide added is 100 mg, 500 mg and 2 g, the morphology of the copper thiovanadate-based materials obtained forms various flower-like morphologies under the regulation of organic macromolecules.
[0028] Electrical properties Test method: Using copper thiovanadate-based material, copper thiovanadate, and copper sulfide from Sample 1 as positive electrodes, Mg as the negative electrode, and MACT as the electrolyte, full cells were assembled. Charge-discharge tests were conducted using a Xinwei charge-discharge apparatus at current densities of 50 mA / g and 200 mA / g, respectively. Figure 12 As shown, when the positive electrode is the copper thiovanadate-based material of sample 1, the electrochemical performance at a current density of 200 mA / g is as follows. Figure 8As shown in the figure, the electrochemical performance of copper thiovanadate at a current density of 200 mA / g in this test is as follows. Figure 13 As shown in the figure, the electrochemical performance of copper sulfide in this test at a current density of 200 mA / g is as follows. Figure 14 As shown in the figure, the copper thiovanadate heterostructure prepared in Example 1 of this application has an electrical performance of 241 mAh / g after activation at 200 mA / g; the copper thiovanadate prepared in Comparative Example 1 has an electrical performance of 39 mAh / g after activation at 100 mA / g; and the copper sulfide prepared in Comparative Example 2 has an electrical performance of 16 mAh / g after activation at 200 mA / g. In summary, the vanadium-based sulfide heterostructure prepared in this application exhibits excellent electrical properties; compared with single-component copper thiovanadate, the electrical properties are significantly improved.
[0029] The above descriptions are merely embodiments of the present invention, and common knowledge such as specific technical solutions and / or characteristics are not described in detail here. It should be noted that the technical means for solving problems in the above embodiments of the present invention can be used in combination to solve multiple technical problems simultaneously. For those skilled in the art, several modifications and improvements can be made without departing from the technical solutions of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.
Claims
1. A copper thiovanadate-based material, characterized in that: The solution is prepared by adding copper, vanadium, and sulfur sources to an organic macromolecule solution using water as a solvent, followed by hydrothermal reaction and centrifugal drying. The molar ratio of Cu, V, and S provided by the copper, vanadium, and sulfur sources is 3:1:
12. The concentration of organic macromolecules in the solution ranges from 0.083% to 3.23% by mass percentage, and the ratio of Cu provided by the copper source to water in the organic macromolecule solution is 1 mmol: 1 mL.
2. The copper thiovanadate-based material, its preparation method, and its application in magnesium secondary batteries according to claim 1, characterized in that: The organic macromolecule solution is prepared by ultrasonic dissolution of any one or at least two of the following: decaalkyltrimethylammonium bromide, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, heptadecanyltrimethylammonium bromide, and octadecyltrimethylammonium bromide in deionized water.
3. The copper thiovanadate-based material according to claim 1, characterized in that: The copper source is any one or a combination of at least two of the following: copper fluoride, copper chloride, copper bromide, copper nitrate, copper sulfate, copper carbonate, copper oxalate, copper acetate, basic copper carbonate, copper hydroxide, copper oxide, copper sulfide, and copper acetylacetonate.
4. The copper thiovanadate-based material according to claim 1, characterized in that: The vanadium source is any one or a combination of at least two of ammonium metavanadate, vanadium acetylacetonate, and sodium orthovanadate.
5. The copper thiovanadate-based material according to claim 1, characterized in that: The sulfur source is any one or a combination of at least two of thioacetamide, thiourea, and L-cysteine.
6. The copper thiovanadate-based material according to claim 1, characterized in that: The hydrothermal reaction temperature is 160-230℃, and the reaction time is 18-72 hours.
7. A method for preparing copper thiovanadate-based materials, characterized in that: Includes the following steps: S1 solution is prepared by dissolving organic macromolecules in deionized water to obtain an organic macromolecule solution, wherein the concentration of organic macromolecules ranges from 0.083% to 3.23% by mass percentage. In the S2 hydrothermal reaction, copper, vanadium, and sulfur sources are added to the organic macromolecular solution prepared in S1, and the reaction is carried out at 160-230℃ for 1-3 days. The molar ratio of Cu, V, and S provided by the copper, vanadium, and sulfur sources is 3:1:12, and the ratio of Cu in the copper source to deionized water in the organic macromolecular solution is 1 mmol: 1 mL. S3 Centrifugation and Drying: After cooling the solution from step S2, centrifugation and drying are performed sequentially to obtain copper thiovanadate-based material.
8. The method for preparing copper thiovanadate-based materials according to claim 7, characterized in that: In S3, during centrifugation, deionized water and ethanol are used alternately for 2-5 centrifugations at a speed of 8000-12000 rpm, with each centrifugation lasting 0 min. The supernatant is discarded after each centrifugation.
9. The method for preparing copper thiovanadate-based materials according to claim 8, characterized in that: In S3, the drying process conditions are: drying in a vacuum oven at 50-70℃ for 10-15 hours, with the vacuum degree of the vacuum oven not lower than 0.09 MPa.
10. The application of the copper thiovanadate-based material obtained by any one of the preparation methods according to claims 7-9 in magnesium secondary batteries.